Simulation of Quantum Algorithm Using Modified Qubit Rotation - Sombillo, Neris I. (Archīum Ateneo, 2023)
We study the implementation of Grover's algorithm in an Ising spin chain quantum computer. In our scheme, we removed the application of time delay whenever a qubit operation is performed. Instead, we introduced a set of modified pulses that utilizes the interaction of the neighboring qubit. In principle, the absence of time delay pulses allows the overall rotation pulses to be applied simultaneously to execute a gate. We show that the fidelity remains high after continuous application of π/2 pulses. The error arising from the unitary evolution is minimized by using soft pulses. Finally, the probability of finding the target state remain bounded through the application of fixed-point quantum search scheme.